Tissue thickness measurements for objective classification of lamb carcasses based on lean meat percentage - Cadavez, Vasco (2009)
The objectives of this study were to analyze the interrelationships among hot carcass weight (HCW), carcass dimension, and tissues thickness and area measurements, and to develop models to predict lean meat percentage of lamb carcasses. One hundred and twenty-five lambs, 83 males and 42 females, of Churra Galega Bragançana Portuguese local breed were slaughtered, and carcasses were weighed (HCW) approximately 30 min after exsanguination. After cooling at 4 C for 24- h a set of seventeen carcass measurements were recorded, and left side of carcasses was dissected and lean meat percentage (LMP) was calculated. Data interrelationships were analyzed following the common factor analysis procedure, and models to predict LMP were developed by regression procedures. All variables were highly and positively correlated with HCW (r > 0.46), being especially high in the carcass dimensions measurements (r > 0.75). Three common factors (factor I = carcass weight; factor II = subcutaneous fat thickness; factor III = breast bone tissues thickness) were retained, and accounted for 83.5% of the variation in the original variables. The best single predictor was C12 fat measurement, and accounted for 66.2% of the LMP variation with a sep of 2.39%. This study shows that prediction of LMP of lamb carcasses can be based on one single fat measurement (C12), If a large set variables is available, their orthogonal CF can be used as predictors avoiding collinearity, and given rise to more stable prediction models.